Naked neck chickens fed with flour Morus alba and Pigeon pea - Solís-Barros, Tito (2017)
To study the productive behavior of heterozygous naked neck chickens fed with Morus alba leaf meal and Cajanus cajan grains roasted at 120 °C for 12 min, we used 144 sexed chickens from the T451N strain from 1 to 90 d of age. The chickens were distributed in three treatments, 48 chickens per treatment distributed in eight replicates. According to random block design. The chickens were raised on floor, in rustic facilities. Productive indicators such as food consumption, average daily weight gain, feed conversion and nutrient use efficiency were evaluated. The treatments were: T1=Control, T2=5% Cajanus cajan and 3% Morus alba and T3=3% C. cajan and 5% M. alba. Control consumed maize and soy, as a dietary basis. The t3 presented the highest food intake (p